Geração de segundo harmônico em compostos hidrazônicos - Araújo, Raiane Sodré de (2016)
In this work, we investigated the phenomenon of second harmonic generation in hydrazone compounds. Based on optical absorption measurements, we determined the energy bands corresponding to the first excited state and the energy gap of the compound. Using the X-ray powder diffraction method, we verified the crystalline nature of the samples. The process of second harmonic generation exhibited by these compounds was characterized by the Kurtz and Perry powder method. We noted that these materials have good efficiency at second harmonic generation, being comparable to KDP. The results indicate that these are promising compounds for the development of photonic applications based on second-order nonlinear optical effects.